Peran Kebijakan dalam Meningkatkan Kualitas Pembelajaran - Laila Ali Tanjung; Arimbi Syahkila Simangunsong; Tengku Darmansah; Yusuf Ali Ahmad Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the role of policy in improving the quality of learning using a qualitative approach. The data sources used in this study are literature study sources that include references from journals, books and other articles. In education, public policy functions to provide equal access to education, improve teacher competence, and develop relevant curricula. Quality education policies must adapt to the times, technological advances, and global challenges. Therefore, education policies are very important to produce a generation that is innovative, intelligent, and ready to face the development of a dynamic society.